PENGARUH URBANISASI, PERTUMBUHAN PDB SEKTOR INDUSTRI DAN PERTUMBUHAN PDB SEKTOR TRANSPORTASI TERHADAP POLUSI LINGKUNGAN DI INDONESIA - Nur Phazillah Helda; Abd. Jamal; Taufiq C. Dawood (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2018)
AbstractThis study analyze the effect of urbanization,GDP growth of industrial sector and GDP growth oftransportation sector on environmental pollution inIndonesia. It employed Autoregressive Distributed Lag(ARDL) model on annual time series data from 1994 to2016. Results found that there is a short-term and longtermrelationship between research variables.Furthermore, in the long term variables urbanizationand GDP growth of transportation sector are affectingthe environmental pollution in Indonesia positively andsignificantly. The GDP growth of industrial sector alsohas positive but not significant effect both in long termand short term. Based on these results the studyrecommends that environmental pollution should bediminished by strengthening the transmigrationprogram and creating public green space in urbanenvironments. The study also stressed the importance ofgreen economy policies so that the GDP growth may beincreased without hurt the environment.